Designing for Networked Learning in The Third Space - Parchoma, Gale; Dreaver-Charles, Kristine; Nelson, Dorothea (Proceedings of the International Conference on Networked Learning, 2018)
The focus of the argument in this paper is first situated in an allegory based on Van Gogh’s Expressionist masterpiece, The Yellow House, in that, our argument shares Van Gogh’s theme of looking for a home for a diverse community, engaged in a shared social movement, imagined/acted upon to evoke change. Our argument is fraught with commitments, investments, hopes, debates, rifts, and conflicts involved in the tentative, emergent nature associated with social movements. Within this diverse and contested context, networked learning praxis is set apart from mainstream e-learning and educational technology theories and practices. The problem of designing learning, in general, and designing for networked learning, in particular, is critically examined through a comparison of the projects, histories, and tenets of instructional design (ID) and learning design (LD). Associated notions of teacher-centred, learner-centred, and community/context-centred approaches to design are compared. Contrasts are drawn and commonalities are identified. The shared LD/ID claims that their projects are pedagogically neutral is interrogated. We then introduce Third Space theory as a way to open a dialogue between ID/LD proponents/researcher-practitioners. Third Space theory begins with abandoning aspirations for emergence of consensus from difference, arguably a practical stance to take when dealing with wide-ranging diversities across multicultural, interdisciplinary, international contexts. Having abandoned consensus, Third Space theory is directed toward ‘multilogues’ that promote boundary crossings and hybridisations, which can result in the emergence new “presences”: newly co-constructed ways to identify and accomplish shared goals. If we conceptualise The Third Space as, (Dare we suggest, an Expressionist social movement?), then based on historical examples of earlier social movements, it is relatively safe to suggest that this space too will likely be marked by misunderstandings and incommensurabilities. Third space ‘multilogues’ will involve participants sometimes talking ‘past each other’ rather than ‘with each other.’ We can expect substantive disagreements and retreats to previously held positions prior to arriving at places of mutual recognition, and perhaps even one or more forms of reconciliation. The paper concludes with an invitation for LDs and IDs to enter The Third Space with a view to finding varied, but sustainable, hybridised conceptualisations of design theories and practices that can contribute to designing future opportunities for networked learning across multicultural, multilinguistic, international, interdisciplinary context.